ANALISIS KOREKSI FISKAL ATAS LAPORAN KEUANGAN GUNA MENENTUKAN BESARNYA PAJAK PENGHASILAN BADAN (Studi Kasus Pada Kopkar PT. Gudang Garam Tbk. Kediri “ MEKAR”) - Adelia Putri Suyatno; Sri Luayyi; Fauziyah (Cahaya Ilmu Bangsa, 2024)
Abstrack Fiscal corrections are corrections or adjustments that must be made by taxpayers before calculating Income Tax (PPh) for corporate taxpayers and individual taxpayers. Fiscal correction or fiscal reconciliation is the process of adjusting accounting profits to comply with tax regulations, in order to produce net income that complies with tax regulations. Kopkar PT. Gudang Garam Tbk, Kediri